(untitled) (International Seven Journal of Multidisciplinary, 2023)
This article explores the role of high-performance fiscal leadership, emphasizing how a hands-on leadership style strengthens organizational results and team engagement in complex fiscal environments. It discusses the integration of participative leadership models that balance technical authority with empathy, focusing on critical aspects such as conflict management, technical capacity building, and motivation of multidisciplinary teams. By actively engaging in daily operations and fostering open communication, hands-on leaders cultivate a culture of accountability, continuous learning, and collaboration. This leadership approach equips teams to navigate regulatory complexities effectively while maintaining high motivation and resilience. The article highlights empirical findings and theoretical frameworks supporting the transformative impact of hands-on leadership on fiscal team performance and organizational success.